Working conditions and professional illnesses of the fuel tanker drivers of the Cotera Cargo Company S.A.C. in the period 2016 – 2018 - Rivera Rengifo, Cristhian William (2022)
The purpose of this research is to determine the relationship between working conditions and occupational diseases of fuel tanker drivers in the company Cotera Cargo S.A.C, in the period 2016-2018; being a descriptive correlational study, with a quantitative approach, with a population of 17 workers, and a sample of 8 workers driving tanks. Obtaining as results, that if there is a relationship between the working conditions and professional diseases of the drivers of fuel tankers of the company, linked to the hours of transportation, to their shift and the relationship that exists between their colleagues of work and with the conditions of the vehicle, as well as the mental load and the use of medications; concluding that they are related to a value of p=0.026 and a Pearson correlation of 0.658 at a significance level of 5%.